POLITIK PENGUATAN INSTITUSI PENDIDIKAN TINGGI ISLAM INDONESIA - Darul Abror (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2018)
This study aims to develop scientific treasures on the focus of educational political studies that are not yet familiar in Indonesia, especially regarding the politics of strengthening Islamic education institutions Era of the Minister of Religion K.H.A. Wahid Hasyim Indonesia that has never been studied by anyone, so this study becomes important to study. This study uses